2019
DOI: 10.17085/apm.2019.14.4.434
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative emergence agitation and intraoperative sevoflurane sedation under caudal block in children: a randomized comparison of two sevoflurane doses

Abstract: Background Sub-umbilical surgery under caudal block in conjunction with sevoflurane sedation may be safe in terms of maintaining spontaneous breathing and avoiding complications associated with general anesthesia. However, sevoflurane-induced emergence agitation (EA) continues to be a clinically important phenomenon in children. To compare the incidence of EA in children undergoing sub-umbilical surgery under caudal block with two different doses of sevoflurane. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Studies have revealed a correlation between higher sevoflurane concentrations and increased agitation incidence in children undergoing various surgical procedures. A study comparing agitation scores in children undergoing inguinal hernia repair with caudal block found that children receiving higher doses of end-tidal sevoflurane (2.5%) during face-mask sedation exhibited higher agitation rates compared with children receiving lower doses (1%) [ 18 ]. Another study demonstrated a relationship between the area under the curve of end-tidal sevoflurane concentration over time (EtSevo-time AUC) and ED.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed a correlation between higher sevoflurane concentrations and increased agitation incidence in children undergoing various surgical procedures. A study comparing agitation scores in children undergoing inguinal hernia repair with caudal block found that children receiving higher doses of end-tidal sevoflurane (2.5%) during face-mask sedation exhibited higher agitation rates compared with children receiving lower doses (1%) [ 18 ]. Another study demonstrated a relationship between the area under the curve of end-tidal sevoflurane concentration over time (EtSevo-time AUC) and ED.…”
Section: Discussionmentioning
confidence: 99%
“…EA is a common phenomenon with children after sevoflurane anesthesia. A lot of risk factors may be considered during the development of EA, for example, pain, age, different types of surgery and inhaled anesthetics with fast emergence, and anesthetic techniques such as sevoflurane (Choi et al, 2019). In some research studies, the prophylactic use of analgesics successfully reduced EA after sevoflurane anesthesia, showed that pain may be one of the reasons for EA (Lynch et al, 1998;Kosar et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Inhalation anesthetics are widely used in clinical anesthesia, especially in pediatric anesthesia. 14 The neurotoxicity of inhaled anesthetics to surgical patients is one of the hot issues in clinical anesthesia at present, which is mainly manifested as POCD, neurodegenerative lesions of thalamus neurons, and decreased learning ability. 15,16 The immature brain is the critical period of neural development.…”
Section: Discussionmentioning
confidence: 99%